Penggunaan radionuklid 137Cs dalam kajian hakisan tanih jangka panjang - Mokhtar Jaafar, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
Research on long-term soil erosion was carried out at Little Landside maize field, in Devon, England, using 137Cs fallout as a tracer. Soil sampling programme was undertaken based on transect approach, and soil samples were collected in winter 2004. This study involved measurements of 137Cs contents in soils, and analysis of soil redistribution. The study used the high-purity germanium (HPGe) detector to examine the 137Cs contents in soil samples, and the model mass-balance III for the analysis of soil redistribution. A measurement of the 137Cs content showed that inventory value was lower by 23.4%, compared to reference inventory value (2427.8 Bq m-2), and this result indicated that soil erosion occurred in the study field. An analysis of soil redistribution showed that both transects recorded a total erosion between ca. 92-100 t ha-1 yr-1, and net soil loss rates were calculated at 90-93 t ha-1 yr- 1. The highest total erosion occurred at the top of the slopes (distance between 0-50 m) with an average value of 16.25 t ha-1 yr-1. Gross erosion rates for the study field was 7.2 t ha-1 yr-1, whilst net soil loss was 6.4 t ha-1 yr-1. These results gave a sediment delivery ratio by 89%. The findings of the study can be concluded thus: soil loss in the study field could be considered as very high, and sediment mobility occurred and transported out from the field boundary by surface runoff